Online shopping Customer’s satisfaction evaluation for products of Monata Bluelight Fashion Brand - Doan, Thi Thu Trang (Vietnam-Korea University of Information and Communication Technology, 2024)
Bachelor thesis of Business Administration - E-commerce Management